The Effect of Interactive Video-Assisted Problem Based Learning Model on Computational Thinking Skills Based on Student Activeness - Dinalia Angglena; Andy Sapta; Novi Andri Nurcahyono (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to test the effect of a Problem-Based Learning (PBL) model assisted by interactive videos on the computational thinking skills of second-grade elementary school students in Banyuasin III. Utilizing a quantitative approach with a quasi-experimental method, data were collected through tests and observations. Statistical analysis was performed using SPSS version 26 to examine the causal relationship between the instructional model and learning outcomes. The results demonstrate that students taught with the PBL and interactive video model achieved a significantly higher average computational thinking ability than those taught with a direct instruction model. The novelty of this research lies in its specific integration of interactive video media to scaffold the PBL process for very young learners, a demographic underrepresented in computational thinking research. A key practical implication is the actionable framework it provides for elementary teachers to enhance 21st-century skills by combining collaborative problem-solving with engaging digital visualization tools. The study contributes empirical evidence to the field of primary education technology, validating a multimedia-enhanced PBL strategy as an effective pedagogical intervention for developing foundational computational thinking.